2019
DOI: 10.1111/acps.13029
|View full text |Cite
|
Sign up to set email alerts
|

Classifying suicidal behavior with resting‐state functional connectivity and structural neuroimaging

Abstract: R. Classifying suicidal behavior with resting-state functional connectivity and structural neuroimaging Objective: About 80% of patients who commit suicide do not report suicidal ideation the last time they speak to their mental health provider, highlighting the need to identify biomarkers of suicidal behavior. Our goal is to identify suicidal behavior neural biomarkers to classify suicidal psychiatric inpatients. Methods: Eighty percent of our sample [suicidal (n = 63) and nonsuicidal psychiatric inpatients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 78 publications
(95 reference statements)
2
35
2
Order By: Relevance
“…Several other fMRI studies examined suicidal ideation but did not focus solely on the triple network model. One study found that reduced connectivity in a network including the left OFC, left thalamus, and right thalamus was associated with greater suicidal ideation and behavior scores ( Kim et al, 2017 ), while a study in psychiatric inpatients (not necessarily with MDD) showed reduced connectivity between the right AI and right OFC, but increased connectivity within the left OFC ( Gosnell et al, 2019 ). Similarly, Weng and colleagues found reduced connectivity between the pgACC and both medial and lateral OFC and right middle temporal cortex ( Du et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several other fMRI studies examined suicidal ideation but did not focus solely on the triple network model. One study found that reduced connectivity in a network including the left OFC, left thalamus, and right thalamus was associated with greater suicidal ideation and behavior scores ( Kim et al, 2017 ), while a study in psychiatric inpatients (not necessarily with MDD) showed reduced connectivity between the right AI and right OFC, but increased connectivity within the left OFC ( Gosnell et al, 2019 ). Similarly, Weng and colleagues found reduced connectivity between the pgACC and both medial and lateral OFC and right middle temporal cortex ( Du et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional statistics can only differentiate different groups with suicidal ideation from those without, rather than detect which individual is at risk. New analytical methods, such as machine learning, have been used in an attempt to develop algorithms to classify individual risk [8][9][10][11]. One study used machine learning algorithms based on functional magnetic resonance imaging (fMRI) neural signatures of death-and life-related concepts to detect individuals with suicidal ideation with 91% accuracy [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical suicide risk evaluations primarily rely on retrospective information or selfreports by patients, which are inevitably subjective. Additionally, almost 80% of patients who have attempted suicide did not report their suicidal ideation to their doctors or healthcare providers (11). Therefore, it is challenging to accurately assess the risk of suicidality in patients with BD-II during depressive episodes in clinical practice, highlighting the need to identify reliable and accurate biomarkers for suicidality.…”
Section: Introductionmentioning
confidence: 99%